Role of Electrical Stimulation in Peripheral Nerve Regeneration: A Systematic Review. Issue 3 (18th March 2022) - ElAbd, Rawan; Alabdulkarim, Abdulaziz; AlSabah, Salman; Hazan, Jessica; Alhalabi, Becher; Thibaudeau, Stephanie
Abstract : Background: Functional recovery after peripheral nerve injury is often suboptimal despite the intrinsic permissive growth environment of the peripheral nervous system. The objective of this systematic review is to explore the use of electrical stimulation (ES) for peripheral nerve regeneration. Methods: A systematic literature search was conducted from inception to March 2, 2021 to retrieve articles on ES for peripheral nerve regeneration using the PubMed, Ovid MEDLINE, and Embase databases. Primary outcome measures included objective measures of motor and sensory nerve function. Results: Four randomized control trials, two case reports, and three case series that addressed the aims were identified. The stimulation parameters varied greatly between studies, without an apparent commonality for a given electrical conduit. Outcomes measured included motor (n = 8) and sensory (n = 7) modalities (cold detection, static two-point discrimination, tactile discrimination, and pressure detection), nerve-specific muscle function and bulk, and electromyography (EMG) motor and sensory terminal latency. Different parameters for measurement were utilized and improvement was observed across the studies compared with controls (n = 4) or pre-intervention measurements (n = 5). One randomized control trial reported no benefit of ES and attributed their findings to their stimulation protocol. Complications were documented in three patients only and included wire remnant removal, skin pigmentation, and bone formation. Conclusions: ES in peripheral nerve regeneration is beneficial in improving and accelerating recovery. A meta-analysis was not performed due to the heterogeneity, but all studies showed positive findings and minor to no complications. These results provide a primer for further development of delivery methods.